MASPY: Towards the Creation of BDI Multi-Agent Systems - Mellado, Alexandre L. L.; Fidler, Igor Guilherme; Borges, André Pinz; Alves, Gleifer Vaz (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2023)
Integrating intelligent agents is essential to the design and functionality of numerous modern computing solutions. Several industries and research domains, from health to finance, manufacturing to customer service, are influenced by advances in the area of Intelligent Agents. Therefore, this work presents a Python library for creating systems composed of intelligent agents following the Belief, Desire and Intention paradigm. To develop systems following these characteristics, four base classes were designed. These classes, agent, environment, communication and handler, create and manage the structural part, leaving the design and specific functions to the programmer. This paper shows that, to the best of our knowledge, there is no other library in Python with the same features and functionalities as the one described here.